Performance Management Improvement in Financing Companies (Case Study of The Commercial Business Division Of Pt. Xyz) - Moch Wahyu Ksatria Budi; Nimmi Zulbainarni; Arry Ekananta (Publikasi Indonesia, 2025)
Financial industries is one of the many economic sector which have huge contribution to a country’s GDP (Gross Domestic Products). Financing companies is one of its contributors, hence it needs top performance in order to secure its postion in national benefactors. This study revolves on performance management inside a division in one of Indonesia’s top financing company. The performance management itself relies on several indicators includinh: leadership, environment, motivation, engagment, and satisfaction. Thus, this study aims to explain which indicators affect the employee’s performance the most. This study used data gathered from 90 people inside Commercial Business division, the data collection itself is done by using Google forms and the analysis itself is conducted through SEM-PLS method. The results of this study confirms of how each aforementioned indicators affects employee’s performance. Moreover, work motivation became the only indicator that have slightest impact on employee’s performance inside Commercial Business division.